2013
DOI: 10.1093/mnras/sts652
|View full text |Cite
|
Sign up to set email alerts
|

Testing a hypothesis of the ν Octantis planetary system

Abstract: We investigate the orbital stability of a putative Jovian planet in a compact binary ν Octantis reported by Ramm et al. We re-analyzed published radial velocity data in terms of self-consistent Newtonian model and we found stable best-fit solutions that obey observational constraints. They correspond to retrograde orbits, in accord with an earlier hypothesis of Eberle & Cuntz, with apsidal lines anti-aligned with the apses of the binary. The best-fit solutions are confined to tiny stable regions of the phase s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…Other strips corresponding to the (1:-5:7) MMR are visible too. Such a complex, fractal-like network of unstable strips in the two-dimensional maps may be interpreted as the Arnold web, as described in Guzzo (2005) for the Solar System, and in the binary ν-Octantis (Goździewski et al 2013). To understand even better the position of the system in the parameter space, we present onedimensional REM scans along the semi-major axis for all the three planets separately (Fig.…”
Section: Dynamical Setup Of the Kepler-30 Systemmentioning
confidence: 99%
“…Other strips corresponding to the (1:-5:7) MMR are visible too. Such a complex, fractal-like network of unstable strips in the two-dimensional maps may be interpreted as the Arnold web, as described in Guzzo (2005) for the Solar System, and in the binary ν-Octantis (Goździewski et al 2013). To understand even better the position of the system in the parameter space, we present onedimensional REM scans along the semi-major axis for all the three planets separately (Fig.…”
Section: Dynamical Setup Of the Kepler-30 Systemmentioning
confidence: 99%
“…The controversial geometry of ν Oct has been investigated with increasing depth beginning with Eberle & Cuntz (2010) and subsequently by Quarles, Cuntz & Musielak (2012) and Goździewski et al (2013). Goździewski et al explored the system in considerable detail and found that stable solutions consistent with the Ramm et al results existed but were confined to tiny regions of the phase space.…”
Section: Introductionmentioning
confidence: 99%
“…Chaotic regions can alter the periodicity of the orbit, as well as the orientation of the orbit relative to some reference direction (i.e., precession of Eulerian angles). Goździewski et al [2013] and Migaszewski et al [2012] demonstrated this principle with a chaos indicator (for details, see Section 4.5).…”
Section: Numerical Search For Periodic Orbits and Resonancesmentioning
confidence: 93%
“…This posed a problem for the confirmation of the exoplanet. However, if one considers an exoplanet in retrograde orbit relative to the orbiting binary, then enlarged regions of stability arise, which would be consistent with the putative exoplanet [Eberle and Cuntz, 2010b, Quarles et al, 2012a, Goździewski et al, 2013. The restricted three-body problem has also been applied to P-type or circumbinary exoplanets.…”
Section: Binary Stellar Systems With a Giant Or Terrestrial Exoplanetmentioning
confidence: 99%